Mitigation and Outcomes of Difficult Bag-Mask Ventilation in Critically Ill Children - Daigle, C. Hunter; Laverriere, Elizabeth K.; Bruins, Benjamin B.; Lockman, Justin L.; Fiadjoe, John E.; McGowan, Nancy; Napolitano, Natalie; Shults, Justine; Nadkarni, Vinay M.; Nishisaki, Akira; for the National Emergency Airway Registry for Children: NEAR4KIDS Investigators Pediatric Acute Lung Injury Sepsis Investigators (PALISI) (Journal of Pediatric Intensive Care, 2023)
Difficult bag-mask ventilation (BMV) occurs in 10% of pediatric intensive care unit (PICU) tracheal intubations (TI). The reasons clinicians identify difficult BMV in the PICU and the interventions used to mitigate that difficulty have not been well-studied. This is a prospective, observational, single-center study. A patient-specific data form was sent to PICU physicians supervising TIs from November 2019 through December 2020 to identify the presence of difficult BMV, attempted interventions used, and perceptions about intervention success. The dataset was linked and merged with the local TI quality database to assess safety outcomes. Among 305 TIs with response (87% response rate), 267 (88%) clinicians performed BMV during TI. Difficult BMV was reported in 28 of 267 patients (10%). Commonly reported reasons for difficult BMV included: facial structure (50%), high inspiratory pressure (36%), and improper mask fit (21%). Common interventions were jaw thrust (96%) and an airway adjunct (oral airway 50%, nasal airway 7%, and supraglottic airway 11%), with ventilation improvement in 44% and 73%, respectively. Most difficult BMV was identified before neuromuscular blockade (NMB) administration (96%) and 67% (18/27) resolved after NMB administration. The overall success in improving ventilation was 27/28 (96%). TI adverse outcomes (hemodynamic events, emesis, and/or hypoxemia <80%) are associated with the presence of difficult BMV (10/28, 36%) versus non-difficult BMV (20/239, 8%, p< 0.001). Difficult BMV is common in critically ill children and is associated with increased TI adverse outcomes. Airway adjunct placement and NMB use are often effective in improving ventilation.
Keywords: mask ventilation; hypoxemia; intensive care unit; pediatric critical care; tracheal intubation; adverse events